Peresean as Local Cultural Heritage and Religious Values in Sasak Society - Riyad, Riyadissolihin; Renda, Rapi (Gema Cendekia Institute, 2025)
Peresean is a martial arts tradition typical of the Sasak people in Lombok that contains deep cultural and religious values. This tradition not only depicts physical strength, but also reflects the philosophy of life, such as courage, honor, and self-control. This study aims to examine Peresean as a representation of local culture as well as a manifestation of the religious values of the Sasak people with a cultural anthropological approach. Data were collected through participatory observation, in-depth interviews, and documentation studies in Semoyang Village, Central Lombok. The results of the study show that Peresean has strong spiritual elements, such as the reading of prayers (mentere), fighting ethics that uphold sportsmanship, and its transformation into a means of teaching religious values in the pesantren environment. This tradition is not just a performance or entertainment, but a medium for cultural preservation and character development of the Sasak people, especially the younger generation. Thus, Peresean is a cultural heritage that has not only aesthetic and historical value, but also spiritual and moral, which continues to be relevant in the face of globalization and modernization.